1997
DOI: 10.1097/00006982-199703000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Siderosis

Abstract: Ocular siderosis should be considered in the differential diagnosis of a tonic or Adies pupil. To detect an occult intraocular foreign body, clinicians should not rely exclusively on computed tomography scanning or plain film radiography, but should also use B-mode echography with careful study of the inferior quadrants. In ocular siderosis a preoperative electroretinogram reduction in amplitudes of as much as 40% may be reversible after intraocular foreign body removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Macrophage activity is closely related to the mechanism and prognosis of ocular siderosis. According to previous studies, vision may be excellent in siderosis with ERG amplitudes of up to 50%, and complete reversal is possible following successful removal of the intraocular foreign body in the early stages of the condition and with amplitudes of up to 40% [8, 11]. Over this limit, macrophage activity may be overwhelmed by the amount of iron load, leading to direct cellular toxicity [4].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage activity is closely related to the mechanism and prognosis of ocular siderosis. According to previous studies, vision may be excellent in siderosis with ERG amplitudes of up to 50%, and complete reversal is possible following successful removal of the intraocular foreign body in the early stages of the condition and with amplitudes of up to 40% [8, 11]. Over this limit, macrophage activity may be overwhelmed by the amount of iron load, leading to direct cellular toxicity [4].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular toxicity of an iron-containing foreign body that is retained and even located in the orbit after an injury may produce ocular siderosis and severe progressive visual loss [ 10 , 11 ]. Gerkowicz et al [ 12 ] studied the penetration of iron and found that iron passes from the orbit into the eyeball and accumulates in considerable quantities in the sclera, choroid, retina, ciliary body, and even in the vitreous and corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations include a rust-colored corneal stroma, heterochromia iridis, pupillary mydriasis, uveitis, cataract, lens subluxation, secondary glaucoma, and retinal degeneration. The electroretinogram may be normal or hypernormal early in the disease process, but it gradually decreases in amplitude as the disease progresses [ 10 , 11 ]. Therefore, an exploratory surgery over the suspected area and complete removal of the foreign body by the emergency physician is necessary before the wounds have been sutured.…”
Section: Discussionmentioning
confidence: 99%
“…The electroretinogram (ERG) is the most common means of detecting ocular siderosis [1, 2, 3, 4, 5, 6, 7, 8, 9]. However, there are a few reports describing individual rod and cone ERGs in patients with ocular siderosis [5, 6, 9].…”
Section: Introductionmentioning
confidence: 99%